Numerical study of regime transitions in a fluidized bed. (1st November 2016) - Antonucci, Cristian M.; Borzone, Luis A.
ABSTRACT: In this study computer modeling was carried out using a discrete element model (DEM) with the aim of predicting the transition between the different fluidization regimes in fluidized beds, which is key for the correct design and operation of this type of equipment. The model implemented in this study considered 100, 000 Geldart B particles. The fluid phase was air under atmospheric conditions at various velocities. The model was used to establish and theoretically predict the transition between flow regimes. The results were validated using currently available correlations and by comparison with experimental research based on spectral methods for the internal pressure variations, showing a high degree of concordance with the computed results. Correct predictions were obtained for the minimum fluidization condition and for the initiation of the bubbling and slugging regimes. Information was also generated that goes beyond the original objective, providing insights on the phenomena that could explain bubble formation in the core of the bed, the increased instability, and the effect of pressure fluctuations, deduced from the detailed description of gas velocity, particle velocity, pressure, and phase density fields as a function of time.